Guidelines for the Formalization of Informal Constructions - United Nations (United Nations, 2020)
This publication is a brief, practical and easy-to-read guide, explaining how to structure a programme for the formalization of informal constructions. It shows how to do this in an affordable, reliable, inclusive and timely manner so that governments can meet the Sustainable development Goals (SDGs) by 2030 and implement the New Urban Agenda. The focus is on the formalization process itself, but there are also descriptions of the preparatory work needed to analyze problem magnitude, as well as how to find political acceptance, identify post-formalization factors, and identify the root problems that cause future informality. The causes of informal development include rapid urbanization, lack of affordable housing, poverty, internal migration, conflicts, marginalization, natural disasters, cumbersome authorization processes, serious weaknesses in the private sector, and corruption. Sometimes society’s most vulnerable groups use it “move-up” from poverty, sometimes people desiring better housing use extra-legal processes to avoid flaws in existing land-market legal systems. These factors often lead to more inspections, bureaucracy, penalties, fees and sometimes even imprisonment. When the causes are systemic, these measures are more likely to exacerbate than resolve the problem. This guide will assist in all aspects of the informal construction formalization process, to the benefit of inhabitants, governments and stake holders.